Poly[[[μ-3,3′-(dimethylsilanediyl)dibenzoato][μ-1,1′-(1,4-phenylene)di-1 H -imidazole]zinc] monohydrate] - Huang, Guohui; Bei, Yiling (Acta crystallographica. Section E, Structure reports online, 2012)
The asymmetric unit of the title compound, {[Zn(C₁₆H₁₆O₄Si)(C₁₂H₁₀N₄)]·H(2)O}(n), consists of one Zn(II) ion, two half 3,3'-(dimethyl-silanedi-yl)dibenzoate ligands and two half 1,1'-(1,4-phenyl-ene)di-1H-imidazole ligands. The Zn(II) ion is four-coordinated by two O atoms from two carboxlate ligands, two N atoms from two imidazole ligands. Two Zn(II) ions are bridged by two carboxyl-ate groups in chelating mode, generating a binuclear secondary building unit (SBU), which is further coordinated by two N atoms from two imidazole ligands in monodentate mode. Thus, the binuclear SBUs are further bridged by imidazole ligands in two different directions, giving rise to a chain. The water solvent mol-ecules are hydrogen bonded within the chain along the c axis.